(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The results of numerical modeling of Vibroacoustic Signal (VAS) in this article provide information on the use of vibroacoustic signal (VAS) parameters describing the dynamics of this process to determine the processing ability of metals by cutting, to determine the cause of the unstable process observed during cutting .